Outcomes after superficial temporal artery–middle cerebral artery anastomosis combined with multiple burr hole surgery and dural inversion synangiosis for moyamoya disease in adults - Xu, Dongxiao; Zheng, Bingjie; Wu, Qiaowei; Yao, Jinbiao; Ilyasova, Tatiana; Beilerli, Aferin; Shi, Huaizhang (Frontiers in Surgery, 2022)
Objective Several forms of cerebral revascularization have been carried out to treat moyamoya disease, however, the existing methods are accompanied by a variety of complications. In this study, the authors aimed to evaluate the clinical and angiographic outcomes of a new surgical procedure: superficial temporal artery–middle cerebral artery (STA-MCA) anastomosis combined with multiple burr hole surgery (MBH) and dural inversion synangiosis for the treatment of moyamoya disease in adults. Methods Patients treated for moyamoya disease from August 2019 to July 2021 were retrospectively reviewed. Clinical data, including perioperative complications and follow-up outcomes, were noted. Preoperative and postoperative angiograms were compared, and the diameters of the frontal branch of the superficial temporal artery (F-STA), the deep temporal artery (DTA), the distal superficial temporal artery (STA) before the bifurcation and the middle meningeal artery (MMA) were measured on preoperative and postoperative angiograms. Meanwhile, a Matsushima score was assigned from postoperative angiograms. Results This study included 66 patients (67 hemispheres). During the follow-up period, a median of 18 (IQR, 13-21) months, no stroke or death occurred in any of the patients. The clinical outcomes were excellent in 27 patients (40.9%), good in 34 patients (51.6%), fair in 4 patients (6.0%), and poor in 1 patient (1.5%); the overall rate of favorable clinical outcomes (excellent and good) was 92.5%. The modified Rankin Scale (mRS) score was significantly improved at follow-up (P<0.001). There were 41 hemispheres imaged by cerebral angiography after the operation, at a median postoperative interval of 9 (IQR, 8-12) months; among them, 34 (82.9%) hemispheres had Matsushima scores of grade A and grade B. The average postoperative diameters in the STA, DTA and MMA were increased significantly in 41 hemispheres at follow-up (P<0.001). Sixteen (24.2%) patients suffered from perioperative complications, including focal hyperperfusion syndrome (HS) in 8(12.2%) patients, cerebral infarction in 3(4.5%) patients (including one case accompanied by wound infection), cerebral hemorrhage in 2(3.0%) patients, seizures in 2(3.0%) patients, and subdural effusion in 1(1.5%) patient. Conclusions The procedure of STA-MCA anastomosis combined with MBH and dural inversion synangiosis may be a safe and effective treatment for adult patients with moyamoya disease.